A arte do teatro na educação durante a infância: a percepção dos professores acerca de suas contribuições - Izumi, Camila Tieme [UNESP] (Universidade Estadual Paulista (Unesp), 2010)
Seeking new ways to be used in the process of teaching and learning, he turned a look at alternative lines of research, going to value the arts in education, and inside, there has been a major focus of the relationship to both the theater and education. Currently, the theater has been the subject of research in education and has been also widely used as an educational resource, and its adoption by professionals is based on studies showing the contributions of the theater to child development. The theater, while playing, artistic expression and involves imagination, creation and sociability.This paper presents child development in all its phases, the importance of games, especially the symbolic games, during this process, through the perspective of Jean Piaget, a brief history of the theater within the education and the contributions actuallyits use as methodology of teaching and learning brings to children's development of the early years of elementary school, bringing the discussion as teachers' perception about the real possibility of its use in schools as a way of teaching and learning. This research aimed to understand the dialogic relationship between theater and basic education, emphasizing its most striking features, emphasize its presence in the teaching and learning in basic education, focusing on the early years of primary education; see how the skills developed with drama can help develop cognitive, psychological, social and moral development of children, performing an initial survey on the possibilities of using the theater within the lesson plans for teachers in the first grade of elementary school and learn the opinions of professional education on theresearch subject, being held with four teachers who teach in the first years of elementary education at a public school in Santa Cruz do Rio Pardo, ...(Complete abstract click electronic address below)

Buscando novas maneiras a serem utilizadas nos processos de ensinar e aprender, voltou-se um olhar para linhas de pesquisas alternativas, passando a valorizar a arte na educação, e dentro dela, deu-se grande foco às vertentes da relação teatro-educação. Atualmente, o teatro tem sido alvo de pesquisas em educação e vem sendo também muito utilizado como recurso pedagógico, e sua adoção pelos profissionais da área é baseada em estudos que demonstram as contribuições do teatro para o desenvolvimento infantil. O teatro, enquanto jogo, expressão e representação artística envolve imaginação, criação e sociabilidade. O presente trabalho apresenta o desenvolvimento infantil em todas as suas fases, a importância dos jogos, principalmente os jogos simbólicos, durante esse processo, segundo a visão de Jean Piaget; um breve histórico do teatro dentro da educação e as contribuições que, de fato, sua utilização como metodologia de ensino e aprendizagem traz ao desenvolvimento das crianças dos anos iniciais do ensino fundamental, trazendo como discussão a percepção dos professores sobre a possibilidade real da sua utilização nas escolas, enquanto forma de ensinar e aprender. A presente pesquisa teve como objetivos compreender a relação dialógica entre teatro e educação básica, ressaltando suas características mais marcantes; enfatizar sua presença no processo de ensino e aprendizagem na educação básica, enfocando principalmente os anos iniciais do ensino fundamental; verificar como as habilidades desenvolvidas com o teatro podem auxiliar no desenvolvimento cognitivo, psicológico, social e moral da criança; realizar um levantamento inicial sobre as possibilidades da utilização do teatro dentro dos planos de...(Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Teatro - Educação; Teatro - Metodologia; Crianças - Desenvolvimento; Sociabilidade; Imaginação; Education Theater; Theater as a Method of Teaching and Learning; Child Developmen; Symbolic games; Imagination; Creativity and Sociability